Partnership models and income of micro-small enterprises as Gerbang Emas funds beneficiaries in East Flores Regency - Hironnymus Jati; Indri Astuti; Dominikus Fernandez (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2017)
This study aims to describe the business partnership model in the development of Micro, Small Enterprises (MSE) of the creative economy and to prove and explain if there is or there is not the increase in MSEs income after obtaining Community Block Grant or Bantuan Langsung Masyarakat (BLM) from Gerakan Membangun Ekonomi Masyarakat (Gerbang Emas) (Community Economic Development Movement). The study used cluster sampling method on 16 types of business. From sampling, we got 105 out of 502 MSEs that are BLM from Gerbang Emas program beneficiaries. The data used in this study are primary data obtained by interviews and questionnaires with both open and closed sentences and questions. Descriptive statistical, correlation, and paired sample t-test methods were used for data processing. The results show that 85.85% of the MSEs partner with government agencies, NGOs, and Church, 11.32% of them work in partnership with other MSEs and other institutions, 49% of them partner with distributor, 75% of them partner with raw material supplier, and 8% of them don’t partner with any party. The revenue of MSEs in creative economy sector experienced an average increase of 12.76% from Rp. 4,248,007 in the previous year and there is statistically a strong correlation (0.999) between income before getting BLM and after getting BLM. There is a significant difference between income before and after getting BLM from Gerbang Emas. Gerbang Emas program only focuses on funding or providing capital to MSEs, doesn’t try to give training on financial management in business so that only 48.5% of respondents differentiate or separate the funds for business purposes and for household use. Keywords: Community, Creative Economy, Partnership